HTRA1-related autosomal dominant cerebral small vessel disease. Issue 2 (20th January 2021) - Liu, Jing-Yi; Zhu, Yi-Cheng; Zhou, Li-Xin; Wei, Yan-Ping; Mao, Chen-Hui; Cui, Li-Ying; Peng, Bin; Yao, Ming
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Homozygous or compound heterozygous mutations in high temperature requirement serine peptidase A1 ( HTRA1 ) gene are responsible for cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL). Recently, increasing evidence has shown that heterozygous HTRA1 mutations are also associated with cerebral small vessel disease (CSVD) with an autosomal dominant pattern of inheritance. This study was aimed to analyze the genetic and clinical characteristics of HTRA1 -related autosomal dominant CSVD. Methods: We presented three new Chinese cases of familial CSVD with heterozygous HTRA1 mutations and reviewed all clinical case reports and articles on HTRA1 -related autosomal dominant CSVD included in PUBMED by the end of March 1, 2020. CARASIL probands with genetic diagnosis reported to date were also reviewed. The genetic and clinical characteristics of HTRA1 -related autosomal dominant CSVD were summarized and analyzed by comparing with CARASIL. Results: Forty-four HTRA1 -related autosomal dominant CSVD probands and 22 CARASIL probands were included. Compared with typical CARASIL, HTRA1 -related autosomal dominant probands has a higher proportion of vascular risk factors ( P <  0.001), a later onset age ( P <  0.001), and a relatively slower clinical progression. Alopecia and spondylosis can be observed, but less than those in the typical CARASIL. Thirty-five heterozygous mutations in HTRA1 were reported, most of which were missense mutations. Amino acids located close to amino acids 250–300 were most frequently affected, followed by these located near 150∼200. While amino acids 250∼300 were also the most frequently affected region in CARASIL patients, fewer mutations precede the 200th amino acids were detected, especially in the Kazal-type serine protease domain. Conclusions: HTRA1 -related autosomal dominant CSVD is present as a mild phenotype of CARASIL. The trend of regional concentration of mutation sites may be related to the concentration of key sites in these regions which are responsible for pathogenesis of HTRA1 -related autosomal dominant CSVD.